(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Under the conditions of increasing global polarization, religious radicalism, and the growing number of ideological challenges, the development of a balanced state policy in the religious sphere becomes especially relevant. In this context, the Republic of Uzbekistan offers a unique experience in the institutionalization of the principles of freedom of conscience and secularism, based on constitutional guarantees, legal regulation, and humanistic values. The present paper examines the provisions of the Concept of State Policy in the Religious Sphere, which reflect both the theoretical and legal foundations as well as the historical and institutional context of the formation of the corresponding policy course.